2023
DOI: 10.1186/s13023-023-02823-1
|View full text |Cite
|
Sign up to set email alerts
|

Current state of rare disease registries and databases in Australia: a scoping review

Rasa Ruseckaite,
Chethana Mudunna,
Marisa Caruso
et al.

Abstract: Background Rare diseases (RDs) affect approximately 8% of all people or > 400 million people globally. The Australian Government’s National Strategic Action Plan for Rare Diseases has identified the need for a national, coordinated, and systematic approach to the collection and use of RD data, including registries. Rare disease registries (RDRs) are established for epidemiological, quality improvement and research purposes, and they are critical infrastructure for clinical trials. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Investing in the infrastructure and staffing would assist in streamlining and simplifying the maintenance and data entry demands of RDRs across Australia. Finally, RDRs should be promoted in hospitals and relevant clinics, and collaborations with relevant international registries should be sought [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investing in the infrastructure and staffing would assist in streamlining and simplifying the maintenance and data entry demands of RDRs across Australia. Finally, RDRs should be promoted in hospitals and relevant clinics, and collaborations with relevant international registries should be sought [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies were conducted to describe the current state of the RDRs capturing Australian data. The first study was a scoping review of the literature in which we identified seventy-four RDRs [ 11 ]. The present study aims to explore data captured by the RDRs identified in the scoping review, to describe registry impact, barriers and enablers of data collection, registry funding, and the future potential of RDRs to improve patient outcomes, facilitate research and clinical trials and provide ongoing surveillance.…”
Section: Introductionmentioning
confidence: 99%